2015
DOI: 10.1212/wnl.0000000000001642
|View full text |Cite|
|
Sign up to set email alerts
|

Neurofilament light chain

Abstract: Objective:To test blood and CSF neurofilament light chain (NfL) levels in relation to disease progression and survival in amyotrophic lateral sclerosis (ALS).Methods:Using an electrochemiluminescence immunoassay, NfL levels were measured in samples from 2 cohorts of patients with sporadic ALS and healthy controls, recruited in London (ALS/control, plasma: n = 103/42) and Oxford (ALS/control, serum: n = 64/36; paired CSF: n = 38/20). NfL levels in patients were measured at regular intervals for up to 3 years. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

60
474
4
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 461 publications
(545 citation statements)
references
References 32 publications
60
474
4
7
Order By: Relevance
“…Previous studies on ALS patients reported stable NfL levels, but showed an increase over time for a subset of patients with a rapid disease progression 17, 42, 43. Serum NfL levels have also been shown to progressively increase in sporadic PPA patients 44.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Previous studies on ALS patients reported stable NfL levels, but showed an increase over time for a subset of patients with a rapid disease progression 17, 42, 43. Serum NfL levels have also been shown to progressively increase in sporadic PPA patients 44.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, the strong association between CSF NfL and survival supports the use of NfL as a prognostic marker. NfL can now be reliably measured in serum and plasma, which is collected less invasively than CSF, making it promising for clinical use, especially when frequent measures are needed 17, 18, 41…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been various ALS biomarker studies published with more ongoing, with special attention focused on identifying biomarkers in CSF or serum. Most of these studies have examined changes of individual biomarkers that might distinguish patients with ALS from healthy control subjects (Lu et al., 2015; Takahashi et al., 2015), but it is likely more appropriate to identify panels of biomarkers rather than focusing on a single factor to increase their specificity to ALS. Some studies were limited by the number of samples in the analysis (Turner et al., 2013), and some chose a different control population into the study (Tateishi et al., 2010).…”
Section: Introductionmentioning
confidence: 99%
“…NfL levels are increased in the cerebrospinal fluid (CSF) of MS patients as well as in degenerative and traumatic neurological diseases (eg, dementia, amyotrophic lateral sclerosis, and spinal cord injury) 4, 5, 6, 7, 8, 9. CSF NfL levels are further increased during relapses and are positively associated with magnetic resonance imaging (MRI) lesion load and disability scores in MS 10, 11, 12.…”
mentioning
confidence: 99%